A TD-DFT study of a class of D–π–A fluorescent probes for detection of typical oxidants. Issue 2 (16th December 2022) - Li, Dezhong; Lei, Da; Ren, Wenfei; Li, Jiguang; Yang, Xinyi; Cai, Zhenzhen; Duan, Haiming; Dou, Xincun
Abstract : The electronegative R-benzene group modulated interaction between the π-bond and MnO4 −, ensuring an effective fluorescence-off response toward KMnO4 . Abstract : A deep understanding of the fluorescence response mechanisms is the foundation for design-oriented strategies for D–π–A probes for trace hazardous chemicals. Here, from the perspective of electronegativity regulation of the π-bridge recognition site, an electron-donation modulation strategy involving various comprehensive evaluations of the optical and chemical properties is proposed through a series of theoretical analyses. Due to the preferential combined interaction between the π-bridge recognition site and MnO4 −, high electrophilic reactivity and feasible chemical reaction energy barrier, a high-performance filter paper chip and hydrogel chip for the detection of aqueous and air-suspended environmental KMnO4 was achieved. We expect the present modulation strategy will facilitate efficient fluorescent probe design and provide a universal methodology for the exploration of functional D–π–A molecules.